(untitled) (Research, Society and Development, 2021)
Objectives: to analyze the discourses that promote the permanence of the elderly in the health labor field, after retirement. Methodology: descriptive exploratory qualitative study carried out in a city in the interior of the state of Rio Grande do Sul, with 16 health professionals aged 60 years or older, both working in Basic Health Units and in hospitals. For data collection, semi-structured interviews were used and for data analysis, Content Analysis was used. Results: four positive aspects were highlighted regarding the maintenance of work activities in the field of health, which concern issues of professional and personal satisfaction, cultivation of social relationships, maintenance of activities of daily living and with regard to contribution to society. From another perspective, there were three negative points that, in a way, oblige them to remain in work activity, mainly related to economic needs, fear of identity loss and anxieties about invisibility and social isolation. Final Considerations: therefore, working gives them encouragement and promotes quality of life, however, reasons emerge that oblige them to remain in a work environment, to meet basic human needs and family economic conditions.